2017
DOI: 10.1038/ng.3836
|View full text |Cite
|
Sign up to set email alerts
|

IFN-λ3, not IFN-λ4, likely mediates IFNL3–IFNL4 haplotype–dependent hepatic inflammation and fibrosis

Abstract: Genetic variation in the IFNL3-IFNL4 (interferon-λ3-interferon-λ4) region is associated with hepatic inflammation and fibrosis. Whether IFN-λ3 or IFN-λ4 protein drives this association is not known. We demonstrate that hepatic inflammation, fibrosis stage, fibrosis progression rate, hepatic infiltration of immune cells, IFN-λ3 expression, and serum sCD163 levels (a marker of activated macrophages) are greater in individuals with the IFNL3-IFNL4 risk haplotype that does not produce IFN-λ4, but produces IFN-λ3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 43 publications
10
79
0
Order By: Relevance
“…Further, considering both genotypes together (rs12979860 CC and rs8099917 TT), we also found this association to be significant, suggesting and additive effect on liver inflammation in patients harboring both genotypes. As these polymorphisms are close to IFN-λ3, which has been involved in the modulation of antiviral responses [13] [26] [27] [28], our results, in agreement with a recent report concluding that IFN-λ3 rather than IFN-λ4 likely mediates haplotype-dependent hepatic inflammation and fibrosis [29], support the hypothesis that this interferon is contributing to a stronger immune response to HCV during the acute infection phase, favoring the spontaneous clearance. Moreover, they also suggest a role for this cytokine in the chronic infection inducing a favorable outcome to the antiviral therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Further, considering both genotypes together (rs12979860 CC and rs8099917 TT), we also found this association to be significant, suggesting and additive effect on liver inflammation in patients harboring both genotypes. As these polymorphisms are close to IFN-λ3, which has been involved in the modulation of antiviral responses [13] [26] [27] [28], our results, in agreement with a recent report concluding that IFN-λ3 rather than IFN-λ4 likely mediates haplotype-dependent hepatic inflammation and fibrosis [29], support the hypothesis that this interferon is contributing to a stronger immune response to HCV during the acute infection phase, favoring the spontaneous clearance. Moreover, they also suggest a role for this cytokine in the chronic infection inducing a favorable outcome to the antiviral therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Growing literature demonstrates genetic associations between rs368234815 or its linked variants with other clinical phenotypes, such as relapse on DAA treatment of HCV (12), liver fibrosis (13, 14), hepatic metallothionein expression (15), post-partum immune activation (16, 17), risk of mucinous ovarian cancer (18), etc. Although other, invariantly expressed type-III IFNs might be also important for these phenotypes, only IFN-λ4 is directly and most dramatically affected by the associated variant, rs368234815, that either creates or eliminates IFN-λ4.…”
Section: Introductionmentioning
confidence: 99%
“…After the adjustment of all the co-variates, the association persisted, indicating that there was no recruitment bias and that resistant genotype frequencies between groups were not influenced by ancestry. The rs12979860 has been the most important polymorphism in the region (Eslam et al, 2017). When, we arranged the haplotypes, including this SNP, our analysis showed that C-C combination at rs8109886 and rs12979860 demonstrated that the likelihood of abnormal CZS was reduced 14.3 times (OR = 0.07).…”
Section: Discussionmentioning
confidence: 86%